If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8k + 12 = 52 Reorder the terms: 12 + 8k = 52 Solving 12 + 8k = 52 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 8k = 52 + -12 Combine like terms: 12 + -12 = 0 0 + 8k = 52 + -12 8k = 52 + -12 Combine like terms: 52 + -12 = 40 8k = 40 Divide each side by '8'. k = 5 Simplifying k = 5
| -7x-28=-98 | | (2x-6)(2x-3)=0 | | 157*=2 | | log[3](2x+1)=2 | | 2xy^2-6x-3y=0 | | 12m^3-6m^2+3m= | | 3x=sqr(6) | | 3x=sqrt(6) | | 30=223/x | | -7x-11=16-8x | | Y^2=6y-9 | | 6(2x+1)=1 | | 18a^2b+27ab^2= | | -140=-5x+5(3x-16) | | 10-x=3x+24 | | 1x+1=2x-8 | | x^2-0.00469x+0.0002345=0 | | 12x^3y^4-39x^4y^3= | | -31-5x=15-7x | | 3-x=x^2+15 | | 2g+3=5 | | -4(5y-6)+2(3y+8)= | | .3x+.4=.5x-.8 | | 3x-6+2x+11=45 | | 3x-6+2x+11=90 | | 4+3=28 | | 8(6x-18)=-432 | | 3x-6+2x+11=42 | | 3x-6+2x+11=17 | | -13x-8=25-2x | | 11u+v-4u+12v= | | 555555555555555x+y=0 |